Adhesives, separators, plates, electrode assemblies, battery cells, batteries and power consuming devices

The combination of an organic polymer and inorganic material with tailored vitrification transition temperatures addresses poor adhesive performance in conventional battery adhesives, improving bonding and safety in batteries.

JP2025511417AInactive Publication Date: 2025-04-16CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023570171
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-06-05
Publication Date
2025-04-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional battery adhesives exhibit poor adhesive performance, leading to ineffective bonding of battery components, which deteriorates dynamic performance and poses safety risks.

Method used

An adhesive comprising an organic polymer and an inorganic material with specific vitrification transition temperatures, ranging from -10 to 95°C, is developed to enhance bonding under battery operating conditions.

Benefits of technology

The adhesive provides improved adhesive performance, reducing separator hole blocking and manufacturing costs while enhancing dynamic and safety performance of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511417000001_ABST
    Figure 2025511417000001_ABST
Patent Text Reader

Abstract

This application discloses an adhesive, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device, which are related to the field of battery technology. The adhesive includes an organic polymer and an inorganic material, and the adhesive includes a first glass transition temperature and a second glass transition temperature in the range of -10 to 95°C, and the first glass transition temperature is higher than the second glass transition temperature. Due to the cooperation of the organic polymer and the inorganic material, the obtained adhesive has good adhesive performance and a suitable glass transition temperature, which is suitable for fully exerting its adhesive performance under the operating conditions of the battery, and further contributes to improving the dynamic performance and safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to a PCT patent application submitted to the China Patent Office on January 4, 2023, bearing application number 202310015629.2 and entitled "ADHESIVE AND RELATED SEPARATOR, ELECTRODE, BATTERY, BATTERY MODULE, BATTERY PACK AND POWER CONSUMPTION DEVICE," the entire contents of which are incorporated herein by reference.

[0002] The present application relates to the field of battery technology, and in particular to adhesives, separators, plates, electrode assemblies, battery cells, batteries, and power consuming devices. [Background technology]

[0003] In recent years, batteries have become more and more widely used. They are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. However, the battery adhesives used in conventional technologies have a problem of poor adhesive performance, which further causes the battery components to be ineffectively bonded, thereby deteriorating the dynamic performance of the battery and causing safety issues. Summary of the Invention

[0004] The present application has been made in view of the above problems, and its object is to provide a material that can provide good adhesive performance under conditions suitable for battery processing, thereby contributing to improving the dynamic performance and safety performance of the battery.

[0005] To achieve the above objectives, embodiments of the present application provide an adhesive, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device.

[0006] According to a first aspect, an embodiment of the present application provides an adhesive, the adhesive comprising an organic polymer and an inorganic material, the adhesive comprising a first vitrification transition temperature and a second vitrification transition temperature within a range of −10 to 95° C., the first vitrification transition temperature being greater than the second vitrification transition temperature.

[0007] As a result, in the technical solutions of the embodiments of the present application, the adhesive obtained by the cooperation of the organic polymer and the inorganic material has good adhesive performance and also has a suitable glass transition temperature, which is suitable for fully exerting its adhesive performance under the operating conditions of the battery, and further contributes to improving the dynamic performance and safety performance of the battery.

[0008] The glass transition temperature is the temperature at which a high polymer transitions from a high elasticity state to a glassy state, and refers to the transition temperature of an amorphous polymer (including the non-crystalline portion of a crystalline polymer) from a glassy state to a high elasticity state or from the latter to the former, and is the lowest temperature of free movement of the amorphous polymer polymer chain segment, generally represented by Tg. The glass transition temperature is one of the important process indicators of a high polymer. When the temperature is above the glass transition temperature, the high polymer shows elasticity, and when the temperature is below the glass transition temperature, the high polymer shows brittleness. The first glass transition temperature of the adhesive proposed in this application is 30 to 75°C, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery.

[0009] In an optional embodiment, the first vitrification transition temperature of the adhesive is between 30 and 75°C, and the second vitrification transition temperature of the adhesive is between -10 and 25°C.

[0010] Therefore, if the vitrification temperature of the adhesive is too low, the material will be too soft and there will be a risk of blocking holes in the separator; if the vitrification temperature of the adhesive is too high, it will cause difficulties in manufacturing the separator and increase the cost of the separator. The adhesive of the present application has two vitrification temperatures, high and low, which gives the adhesive the advantages of having two vitrification temperatures, greatly reducing the risk of blocking holes in the adhesive and reducing the manufacturing cost of the separator.

[0011] In any embodiment, the inorganic material is attached to the surface of the organic polymer and / or dispersed within the organic polymer, so that, with the organic polymer as the skeleton, the inorganic material may be simultaneously dispersed within and on the surface of the organic polymer, or may be distributed only within the organic polymer, or may be distributed only on the surface of the organic polymer, making the adhesive suitable for fully exerting its adhesive performance under battery operating conditions, and further contributing to improving the dynamic performance and safety performance of the battery.

[0012] In an optional embodiment, the polymerized monomers of the organic polymer include a first monomer, the structural formula of the first monomer being: JPEG2025511417000002.jpg4153 where R1 contains a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, R2 contains a substituted or unsubstituted alkyl group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or an isobornyl group, and in the case of substitution, the substituent contains a hydroxyl group or an alkyl group having 1 to 6 carbon atoms. Thereby, the unsaturated ester group in the first monomer can improve the compatibility of the polymer with the electrolyte and reinforce the ion conduction ability, and as a flexible monomer chain segment in the molecular chain segment, it can adjust the glass transition temperature of the organic polymer and improve the toughness when the adhesive is applied, contributing to exerting a good adhesive action.

[0013] In any embodiment, the first monomer comprises at least one of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate and trimethylolpropane triacrylate. Experiments have shown that the use of at least one of the above organic substances for polymerization can further adjust the glass transition temperature of the organic polymer and improve the toughness of the adhesive during application, which contributes to better adhesion.

[0014] In an optional embodiment, the first monomer comprises at least one of methyl methacrylate, lauryl acrylate, lauryl methacrylate and trimethylolpropane triacrylate, which can further adjust the glass transition temperature of the organic polymer and improve the toughness of the adhesive during application, thereby contributing to better adhesion.

[0015] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer, the second monomer including an organic material containing an unsaturated nitrile group, the organic material containing an unsaturated nitrile group having a cyano group with strong polarity, and contributing to improving ionic conductivity.

[0016] In an optional embodiment, the polymerized monomers of the organic polymer further include a third monomer, the third monomer including an organic material containing an unsaturated amide group, and serves to improve electrolyte resistance.

[0017] The polymerized monomers of the organic polymer further include a fourth monomer, the fourth monomer including an organic material containing an unsaturated alkenyl group to further adjust the molecular weight.

[0018] In an optional embodiment, the polymerized monomers of the organic polymer further comprise a second monomer, the structural formula of the second monomer being: JPEG2025511417000003.jpg3540Here, R3 contains a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the organic substance containing an unsaturated nitrile group has a cyano group with strong polarity, which contributes to improving ionic conductivity.

[0019] The polymerized monomers of the organic polymer further include a third monomer, and the structural formula of the third monomer is as follows: JPEG2025511417000004.jpg4152Here, R4 includes a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R5 includes a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms, and the third monomer includes an unsaturated amide group and serves to improve electrolyte resistance.

[0020] The polymerized monomers of the organic polymer further include a fourth monomer, and the structural formula of the fourth monomer is as follows: JPEG2025511417000005.jpg4346Here, R6, R7, R8, and R9 each independently comprise a hydrogen atom, a substituted or unsubstituted phenyl group, a substituted or unsubstituted cycloalkyl group, or a linear or branched alkyl group, and the fourth monomer comprises an unsaturated alkenyl group and further adjusts the molecular weight.

[0021] In an optional embodiment, the second monomer comprises at least one of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and further comprises at least one of acrylonitrile and methacrylonitrile, and as can be seen from the experiment, the second monomer adopts at least one of the above organic materials, which can further adjust the vitrification temperature and improve the electrolyte resistance.

[0022] In any embodiment, the third monomer comprises an organic material containing an unsaturated amide group, specifically, the third monomer comprises at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide, and the third monomer comprises at least one of acrylamide and N-methylolacrylamide. Experiments have shown that the third monomer employs at least one of the above organic materials and can further play a role in controlling molecular weight.

[0023] In an optional embodiment, the fourth monomer comprises at least one of ethylene, styrene, butadiene and isoprene. Experiments have shown that the fourth monomer can adopt at least one of the above organic materials to further adjust the vitrification temperature and improve the electrolyte resistance.

[0024] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer and a third monomer, the second monomer includes an organic material containing an unsaturated nitrile group, the third monomer includes an organic material containing an unsaturated amide group, and the fourth monomer includes an organic material containing an unsaturated alkenyl group, and a weight ratio of the first monomer, the second monomer, and the third monomer is 1:0-0.8:0-0.15.

[0025] The organic polymer is obtained by polymerizing a first monomer, a second monomer and a third monomer with different functional groups according to a certain ratio, and the obtained organic polymer can fully exert the advantages of each polymer monomer, so that the adhesive polymer containing it has good adhesive performance, and has a relatively low glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0026] In any embodiment, the weight ratio of the first monomer, the second monomer, and the third monomer is 1:0.05-0.2:0.05-0.1, which further contributes to improving the dynamic performance and safety performance of the secondary battery.

[0027] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer, a third monomer, and a fourth monomer, the second monomer includes an organic material containing an unsaturated nitrile group, the third monomer includes an organic material containing an unsaturated amide group, and the fourth monomer includes an organic material containing an unsaturated alkenyl group, and a weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0-0.8:0-0.7:0-0.5.

[0028] The addition of the fourth monomer further enriches the monomer variety of the organic polymer, and allows it to exert the effect of unsaturated alkenyl groups, so that the adhesive polymer containing it has good adhesive performance and has a relatively low glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0029] In any embodiment, the weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0.05-0.6:0.05-0.3:0-0.2. The above blending ratios lower the resistance of the separator, increase the ionic conductivity of the separator, and improve the battery performance.

[0030] In any embodiment, the particle size of the adhesive satisfies 3 μm≦D50≦10 μm. If the particle size D50 of the adhesive is larger than 10 μm, the particle size is too large, which will increase the gap between the separator and other components, affect the battery charge / discharge rate, and occupy more of the internal volume of the battery core, affecting the energy density of the battery core. If the particle size is too small, it will block the holes on the separator. Therefore, a particle size in the above range is more suitable.

[0031] The particle size distribution of the adhesive is (D90-D10) / D50, and the particle size distribution is less than or equal to 2.5. The particle size distribution indicates the uniformity of the adhesive particles. The larger the particle size distribution, the more non-uniform the adhesive particles are. If the particle size distribution is greater than 2.5, even if small particles are filled in the middle of the gaps between the large particles, the small particles will not function and will block the holes, resulting in waste.

[0032] The particle size of the inorganic material is between 0.0001 μm and 2 μm. The particle size of the inorganic material is between 0.0001 μm and 2 μm, so that the inorganic material and the organic polymer are thoroughly mixed, and thus the inorganic material has a relatively low density, excellent thermal stability and chemical stability, and the surface of the material has more active functional groups, which can improve the separator electrolyte wettability, accelerate the ion transmission rate and enhance the electrochemical performance of the battery.

[0033] In any embodiment, the particle size distribution of the adhesive is (D90-D10) / D50, the particle size distribution is smaller than 2, and the particle size of the inorganic material is 0.01 μm to 0.5 μm. In the above-mentioned particle size limiting situation, it is possible to further improve the separator electrolyte wettability, accelerate the ion transmission rate, and improve the electrochemical performance of the battery.

[0034] In any embodiment, the particle size distribution of the adhesive is (D90-D10) / D50, the particle size distribution is smaller than 1.8, and the particle size of the inorganic material is 0.01 μm to 0.2 μm, and within the above range, the performance of each aspect of the adhesive is relatively good.

[0035] In any embodiment, based on the mass of the adhesive, the mass occupancy of the organic polymer is 50% to 99.9%, and thus the organic polymer and the inorganic material bond with each other and play important roles, allowing the adhesive to have good adhesive performance, thereby contributing to improving the dynamic performance and safety performance of the battery.

[0036] The inorganic material includes at least one of silicon oxide, aluminum oxide, calcium oxide, zinc oxide, magnesium oxide, sodium sulfate, sodium benzoate, calcium carbonate and its modified materials. By adopting at least one of the above inorganic materials, the adhesive has good adhesive performance, thereby contributing to improving the dynamic performance and safety performance of the battery.

[0037] In an optional embodiment, based on the weight of the adhesive, the weight occupancy of the organic polymer is 60% to 99%, and the inorganic material includes at least one of fumed silicon dioxide, silicon fine powder, aluminum oxide, and sodium benzoate, under the above conditions, the adhesive has relatively good adhesive performance, and further improves the dynamic performance and safety performance of the battery.

[0038] In some embodiments, based on the mass of the adhesive, the mass occupancy of the organic polymer is 70% to 99%, and thus the organic polymer and the inorganic material bond with each other and play important roles, allowing the adhesive to have better adhesive performance, thereby further contributing to improving the dynamic performance and safety performance of the battery.

[0039] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 2 nm to 1 μm. With this particle size, not only does the hole blocking phenomenon not occur, but also contributes to the inorganic material exerting its function.

[0040] In an optional embodiment, the outer surface of the adhesive is provided with an uneven surface, so as to increase the contact area between the adhesive and the separator and other components, and to improve the adhesion effect.

[0041] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 100 nm. The particle size contributes to the inorganic material exerting its effect even more.

[0042] In an optional embodiment, the adhesive has an ionic conductivity of 0.3 to 0.6 mS cm -1 Conductivity is the ability of a solution to conduct electric current, expressed as a number, and is expressed in units of siemens meters (S / m). The ionic conductivity of the adhesive proposed in this application is 0.3-0.6 mS cm -1 The conductive and adhesive properties of the material can be fully utilized, and the kinetic performance of the secondary battery can be further improved.

[0043] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 20 nm. This particle size contributes to the inorganic material exerting its effect even more.

[0044] According to a second aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application.

[0045] According to a third aspect, an embodiment of the present application provides a plate, the plate comprising an adhesive according to an embodiment of the first aspect of the present application.

[0046] According to a fourth aspect, an embodiment of the present application provides an electrode assembly, the electrode assembly including at least one of the adhesive of the embodiment of the first aspect of the present application, the separator of the embodiment of the second aspect, and the electrode plate of the embodiment of the third aspect.

[0047] According to a fifth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to an embodiment of the fourth aspect of the present application.

[0048] According to a sixth aspect, an embodiment of the present application provides a battery, the battery including a battery cell according to an embodiment of the fifth aspect of the present application.

[0049] According to a seventh aspect, an embodiment of the present application provides a power consuming device, the power consuming device comprising a battery cell according to an embodiment of the fifth aspect of the present application or a battery according to an embodiment of the sixth aspect. [Brief description of the drawings]

[0050] In order to more clearly describe the technical solutions in the embodiments of the present invention or the prior art, the following briefly introduces the drawings that need to be used in the embodiments or the prior art description, and it is obvious that the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other related drawings based on these drawings without making creative efforts. The realization of the objectives, functional features and advantages of the present invention will be further described with reference to the drawings in conjunction with the embodiments. [Figure 1] FIG. 1 is a schematic diagram of a battery cell according to one embodiment of the present application. [Diagram 2] FIG. 2 is an exploded view of the battery cell according to the embodiment of the present application shown in FIG. [Diagram 3] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 4] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Diagram 5] FIG. 5 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 4. [Figure 6]1 is a schematic diagram of a power consumption device powered by a secondary battery according to an embodiment of the present application; [Figure 7] FIG. 2 is an SEM image of the adhesive of Example 1 of the present application. [Figure 8] FIG. 2 is another SEM view of the adhesive of Example 1 of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0051] Hereinafter, with appropriate reference to the drawings, embodiments specifically disclosing the adhesive, separator, electrode plate, electrode assembly, battery cell, battery, and power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of structures that are actually the same may be omitted. This is to avoid the following description becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0052] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0053] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, and preferably in sequence. For example, the method includes steps (a) and (b) to mean that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, the method mentioned above may further include step (c) to mean that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0056] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0057] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0058] The inside of a secondary battery is composed of a positive electrode plate, a negative electrode plate, a separator and an electrolyte. In order to optimize the manufacturing process and the performance of the battery core, it is necessary to provide a certain adhesive force between the positive electrode plate, the negative electrode plate and the separator. The way to achieve this is to coat the separator surface with an adhesive coating material to produce an adhesive separator. In the current technology, the material coated on the separator surface can be divided into fluorine-containing polymers and non-fluorine-containing polymers.

[0059] Fluorine-containing polymers are required to be applied to the separator, and the raw material source of the fluorine-containing polymer adhesive is single, resources are gradually depleted, costs are increasingly high, and ozone-depleting substances are used in the manufacturing process, which poses high environmental risks. And the melting point of the fluorine-containing polymer used for applying the separator is high, and the battery core hot pressing temperature is generally below 100°C, which cannot reach the melting point of the fluorine-containing polymer adhesive, so the separator using the fluorine-containing polymer adhesive has relatively poor adhesion to the electrode plate during hot pressing. The density of the fluorine-containing polymer adhesive material is high, and a high coating weight is required. Coating a non-fluorine-containing polymer on the separator generally involves applying a polyester polymer, but the traditional polyester type adhesive has relatively poor adaptability to the battery core manufacturing process. For example, there is a problem of hole blocking in small particle size emulsions or suspensions. There is a problem of poor hot pressing and increased internal resistance of the battery in polyester powders with large particle size and high vitrification temperature.

[0060] That is, the inventors discovered in actual operation that the battery adhesives used in the prior art sometimes have relatively poor adhesive performance and relatively high melting points, making it difficult to fully exert its adhesive effect under battery working conditions and unable to effectively bond battery components, which may cause the components to separate or fall off during use, deteriorating the dynamic performance of the battery and bringing about potential safety hazards.

[0061] Unexpectedly, the inventors discovered after a large amount of experiments that an organic polymer obtained by polymerizing polymer monomers containing specific functional groups in a certain weight ratio has good adhesive properties and is suitable for fully exerting its adhesive properties under battery operating conditions, thereby contributing to improving the dynamic performance and safety performance of secondary batteries. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0062] Seen from the development of the market situation, the application of power battery becomes more and more extensive. Power battery is not only used in energy storage power supply systems such as hydroelectric, thermal, wind and solar power stations, but also widely used in electric transportation tools such as electric bicycles, electric motorcycles, electric cars, and military equipment and aerospace. With the continuous expansion of the application field of power battery, its market demand also continues to increase.

[0063] Based on this, the present application provides an adhesive, a separator, a plate, an electrode assembly, a battery cell, a battery, and a power consuming device.

[0064] According to a first aspect, the present application provides an adhesive, the adhesive comprising an organic polymer and an inorganic material, the adhesive comprising a first vitrification transition temperature and a second vitrification transition temperature in a range of −10 to 95° C., the first vitrification transition temperature being greater than the second vitrification transition temperature.

[0065] At the above glass transition temperature, due to the cooperation between the organic polymer and the inorganic material, the adhesive obtained has good adhesive performance and also has a suitable glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the battery.

[0066] The glass transition temperature is the temperature at which a high polymer transitions from a high elasticity state to a glassy state, and refers to the transition temperature at which an amorphous polymer (including the non-crystalline portion of a crystalline polymer) transitions from a glassy state to a high elasticity state or from the latter to the former, and is the lowest temperature at which the amorphous polymer polymer chain segment can freely move, and is generally represented by Tg. When the temperature is above the glass transition temperature, the high polymer exhibits elasticity, and when the temperature is below the glass transition temperature, the high polymer exhibits brittleness. The first glass transition temperature of the adhesive proposed in this application is 30 to 75°C, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of secondary batteries.

[0067] The vitrification temperature can be measured by methods commonly used in the art, for example, can be tested by differential scanning calorimetry with reference to GB / T 19466.2.

[0068] In an optional embodiment, the first vitrification transition temperature of the adhesive is between 30 and 75°C, and the second vitrification transition temperature of the adhesive is between -10 and 25°C.

[0069] Therefore, in the technical solution of the embodiment of the present application, the first glass transition temperature of the adhesive may be, for example, but not limited to, any one of the following points or a range value between any two of: 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C; the second glass transition temperature of the adhesive may be, for example, but not limited to, any one of the following points or a range value between any two of: -10°C, -5°C, 0°C, 5°C, 10°C, 15°C, 20°C, 25°C; if the glass transition temperature of the adhesive is too low, the material is too soft and there is a risk of blocking the separator holes; if the glass transition temperature of the adhesive is too high, it will cause difficulties in manufacturing the separator and increase the cost of the separator; the adhesive of the present application has two glass transition temperatures, high and low, which gives the adhesive the advantage of having two glass transition temperatures, greatly reducing the risk of blocking the adhesive holes and reducing the manufacturing cost of the separator.

[0070] When the two glass transition temperatures of the adhesive are within the above ranges, the adhesive can fully exert its adhesive performance and provide sufficient adhesive strength to the battery components under the operating conditions of the battery, and avoid the components from being separated or falling off, which would deteriorate the dynamic performance of the battery and cause safety problems.

[0071] In any embodiment, the inorganic material is attached to the surface of the organic polymer and / or dispersed within the organic polymer, so that, with the organic polymer as the skeleton, the inorganic material may be simultaneously dispersed within and on the surface of the organic polymer, or may be distributed only within the organic polymer, or may be distributed only on the surface of the organic polymer, making the adhesive suitable for fully exerting its adhesive performance under battery operating conditions, and further contributing to improving the dynamic performance and safety performance of the battery.

[0072] In an optional embodiment, the polymerized monomers of the organic polymer include a first monomer, the structural formula of the first monomer being: JPEG2025511417000006.jpg3853 where R1 contains a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, R2 contains a substituted or unsubstituted alkyl group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or an isobornyl group, and in the case of substitution, the substituent contains a hydroxyl group or an alkyl group having 1 to 6 carbon atoms. Thereby, the unsaturated ester group in the first monomer can improve the swelling resistance of the polymer, and as a flexible monomer chain segment in the molecular chain segment, it can adjust the glass transition temperature of the organic polymer and improve the toughness when the adhesive is applied, contributing to exerting a good adhesive action.

[0073] In any embodiment, the first monomer comprises at least one of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate and trimethylolpropane triacrylate. Experiments have shown that the use of at least one of the above organic substances for polymerization can further adjust the glass transition temperature of the organic polymer and improve the toughness of the adhesive during application, which contributes to better adhesion.

[0074] In an optional embodiment, the first monomer comprises at least one of methyl methacrylate, lauryl acrylate, lauryl methacrylate and trimethylolpropane triacrylate, which can further adjust the glass transition temperature of the organic polymer and improve the toughness of the adhesive during application, thereby contributing to better adhesion.

[0075] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer, the second monomer including an organic material containing an unsaturated nitrile group, the organic material containing an unsaturated nitrile group having a cyano group with strong polarity, and contributing to improving ionic conductivity.

[0076] In an optional embodiment, the polymerized monomers of the organic polymer further comprise a third monomer, the third monomer comprising an organic material containing an unsaturated amide group, and serves to control molecular weight.

[0077] The polymerized monomers of the organic polymer further include a fourth monomer, the fourth monomer including an organic material containing an unsaturated alkenyl group to further adjust the molecular weight.

[0078] In an optional embodiment, the polymerized monomers of the organic polymer further comprise a second monomer, the structural formula of the second monomer being: JPEG2025511417000007.jpg4046 Here, R3 contains a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, and the organic substance containing an unsaturated nitrile group has a cyano group with strong polarity, which contributes to improving ionic conductivity.

[0079] The polymerized monomers of the organic polymer further include a third monomer, and the structural formula of the third monomer is as follows: JPEG2025511417000008.jpg3953Here, R4 contains a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R5 contains a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms, and the third monomer contains an unsaturated amide group and serves to adjust the molecular weight.

[0080] The adhesive of the present application includes an organic polymer, which is obtained by polymerizing a first monomer having an O=CO group, a second monomer having an unsaturated nitrile group, and a third monomer having an unsaturated amide group according to a certain weight ratio, which is favorable for fully exerting the synergistic advantages of each monomer, and allows the produced organic polymer to have good adhesive performance and two glass transition temperatures, high and low, so that it is suitable for fully exerting its adhesive performance under the operating conditions of the battery, and improves the dynamic performance and safety performance of the secondary battery. The adhesive of the present application further includes an inorganic material, which contributes to improving the flame retardant performance of the adhesive, thereby improving the safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0081] The polymerized monomers of the organic polymer further include a fourth monomer, and the structural formula of the fourth monomer is as follows: JPEG2025511417000009.jpg4246Here, R6, R7, R8, and R9 each independently comprise a hydrogen atom, a substituted or unsubstituted phenyl group, a substituted or unsubstituted cycloalkyl group, or a linear or branched alkyl group, and the fourth monomer comprises an unsaturated alkenyl group and further adjusts the molecular weight.

[0082] The addition of the fourth monomer further enriches the monomer variety of the organic polymer, and allows it to exert the effect of unsaturated alkenyl groups, so that the adhesive polymer containing it has good adhesive performance and has a relatively low glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0083] In any embodiment, the second monomer comprises at least one of acrylonitrile, methacrylonitrile, and ethacrylonitrile, and further, the second monomer comprises at least one of acrylonitrile and methacrylonitrile, and as experimentally proven, the second monomer employs at least one of the above organic materials, which can further improve the ionic conductivity of the adhesive.

[0084] In any embodiment, the third monomer comprises an organic material containing an unsaturated amide group, specifically, the third monomer comprises at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide, and the third monomer comprises at least one of acrylamide and N-methylolacrylamide. Experiments have shown that the third monomer employs at least one of the above organic materials and can further play a role in controlling molecular weight.

[0085] In an optional embodiment, the fourth monomer comprises at least one of ethylene, styrene, butadiene, and isoprene. Experiments have shown that the fourth monomer employs at least one of the above organics and can further function to adjust the molecular weight.

[0086] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer and a third monomer, the second monomer includes an organic material containing an unsaturated nitrile group, the third monomer includes an organic material containing an unsaturated amide group, and the fourth monomer includes an organic material containing an unsaturated alkenyl group, and a weight ratio of the first monomer, the second monomer, and the third monomer is 1:0-0.8:0-0.15.

[0087] The organic polymer is obtained by polymerizing a first monomer, a second monomer and a third monomer with different functional groups in a certain ratio, and the obtained organic polymer can fully exert the advantages of each polymer monomer, so that the adhesive polymer containing it has good adhesive performance, and has a relatively low glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0088] In any embodiment, the weight ratio of the first monomer, the second monomer, and the third monomer is 1:0.05-0.2:0.05-0.1, which further contributes to improving the dynamic performance and safety performance of the secondary battery.

[0089] In an optional embodiment, the polymerized monomers of the organic polymer further include a second monomer, a third monomer, and a fourth monomer, the second monomer includes an organic material containing an unsaturated nitrile group, the third monomer includes an organic material containing an unsaturated amide group, and the fourth monomer includes an organic material containing an unsaturated alkenyl group, and a weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0-0.8:0-0.7:0-0.5.

[0090] The addition of the fourth monomer further enriches the monomer variety of the organic polymer, and allows it to exert the effect of unsaturated alkenyl groups, so that the adhesive polymer containing it has good adhesive performance and has a relatively low glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the secondary battery. Moreover, when the adhesive is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving the battery performance.

[0091] In any embodiment, the weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0.05-0.6:0.05-0.3:0-0.2. The above blending ratios lower the resistance of the separator, increase the ionic conductivity of the separator, and improve the battery performance.

[0092] In any embodiment, the particle size of the adhesive satisfies 3 μm≦D50≦10 μm. If the particle size D50 of the adhesive is larger than 10 μm, the particle size is too large, which will increase the gap between the separator and other components, affect the battery charge / discharge rate, and occupy more of the internal volume of the battery core, affecting the energy density of the battery core. If the particle size is too small, it will block the holes on the separator. Therefore, a particle size in the above range is more suitable.

[0093] As can be understood, in the examples of this application, the particle size corresponding to when the cumulative particle size distribution percentage of the adhesive particles reaches 50% is Dv50, and the test method is as follows:

[0094] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5min to ensure the sample is completely dispersed. Turn on the laser granulometer and test the background automatically after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0095] The particle size distribution of the adhesive is (D90-D10) / D50, and the particle size distribution is less than or equal to 2.5. The particle size distribution indicates the uniformity of the adhesive particles. The larger the particle size distribution, the more non-uniform the adhesive particles are. If the particle size distribution is greater than 2.5, even if small particles are filled between large particles, the small particles will not function and will block the holes, resulting in waste.

[0096] As can be seen, the test method of D50 is as described above, in the examples of the present application, the particle size corresponding to when the cumulative particle size distribution percentage of the adhesive particles reaches 90% is Dv90, and the test method is as follows:

[0097] Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5min to ensure the sample is completely dispersed. Turn on the laser granulometer and test the background automatically after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0098] The particle size of the inorganic material is between 0.0001 μm and 2 μm. The particle size of the inorganic material is between 0.0001 μm and 2 μm, so that the inorganic material and the organic polymer are thoroughly mixed, and thus the inorganic material has a relatively low density, excellent thermal stability and chemical stability, and the surface of the material has more active functional groups, which can improve the separator electrolyte wettability, accelerate the ion transmission rate and improve the dynamic performance of the battery.

[0099] In any embodiment, the particle size distribution of the adhesive is (D90-D10) / D50, the particle size distribution is smaller than 2, and the particle size of the inorganic material is 0.01 μm to 0.5 μm. In the above-mentioned particle size limiting situation, it can further improve the separator electrolyte wettability, accelerate the ion transmission rate, and improve the dynamic performance of the battery.

[0100] In any embodiment, the particle size distribution of the adhesive is (D90-D10) / D50, the particle size distribution is smaller than 1.8, and the particle size of the inorganic material is 0.01 μm to 0.2 μm, and within the above range, the performance of each aspect of the adhesive is relatively good.

[0101] In any embodiment, based on the mass of the adhesive, the mass occupancy of the organic polymer is 50% to 99.9%, and thus the organic polymer and the inorganic material bond with each other and play important roles, allowing the adhesive to have good adhesive performance, thereby contributing to improving the dynamic performance and safety performance of the battery.

[0102] The inorganic material includes at least one of silicon oxide, aluminum oxide, calcium oxide, zinc oxide, magnesium oxide, sodium sulfate, sodium benzoate, calcium carbonate and its modified materials. By adopting at least one of the above inorganic materials, the adhesive has good adhesive performance, thereby contributing to improving the dynamic performance and safety performance of the battery.

[0103] In an optional embodiment, based on the weight of the adhesive, the weight occupancy of the organic polymer is 60% to 99%, and the inorganic material includes at least one of fumed silicon dioxide, silicon fine powder, aluminum oxide, and sodium benzoate, under the above conditions, the adhesive has relatively good adhesive performance, and further improves the dynamic performance and safety performance of the battery.

[0104] In some embodiments, based on the mass of the adhesive, the mass occupancy of the organic polymer is 70% to 99%, and thus the organic polymer and the inorganic material bond with each other and play important roles, allowing the adhesive to have better adhesive performance, thereby further contributing to improving the dynamic performance and safety performance of the battery.

[0105] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 2 nm to 1 μm. With this particle size, not only does the hole blocking phenomenon not occur, but also contributes to the inorganic material exerting its function.

[0106] In an optional embodiment, the outer surface of the adhesive is provided with an uneven surface, so as to increase the contact area between the adhesive and the separator and other components, and to improve the adhesion effect.

[0107] In any embodiment, the weight average molecular weight of the organic polymer is 500,000 to 1,200,000, and further 800,000 to 1,000,000. The molecular weight of the organic polymer can be measured by adopting a method commonly used in the art, for example, by gel permeation chromatography with reference to GB / T 21863-2008.

[0108] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 100 nm. The particle size contributes to the inorganic material exerting its effect even more.

[0109] In an optional embodiment, the adhesive has an ionic conductivity of 0.3 to 0.6 mS cm -1 Conductivity is the ability of a solution to conduct electric current, expressed as a number. It is expressed in units of siemens meters (S / m), and the ionic conductivity of the adhesive proposed in this application is 0.3-0.6 mS cm. -1 The conductive and adhesive properties of the material can be fully utilized, and the kinetic performance of the secondary battery can be further improved.

[0110] The inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 20 nm. This particle size contributes to the inorganic material exerting its effect even more.

[0111] According to a second aspect, an embodiment of the present application provides a separator, the separator comprising an adhesive according to an embodiment of the first aspect of the present application.

[0112] When the adhesive of the first aspect of the present application is used in a separator, it contributes to reducing the resistance of the separator and increasing the ionic conductivity of the separator, thereby improving battery performance.

[0113] The present application is not particularly limited to the type of separator substrate, and any known porous structure separator substrate having good chemical stability and mechanical stability can be selected.

[0114] In some embodiments, the separator substrate may be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film, without any particular limitation. When the separator is a multilayer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0115] The separator of the present application can be manufactured by adopting a conventional method for separators in the art, for example, the adhesive described in the first embodiment of the present application can be dissolved in an organic solvent to obtain a slurry, and the slurry can be applied onto a separator material, and then the organic solvent can be removed through drying and weighing, that is, the separator of the present application can be obtained.

[0116] In some embodiments, the adhesive has a coating density on the separator substrate of 0.3-1.0 g / m 2 and 0.3-0.8 g / m 2 It is.

[0117] According to a third aspect, the present application provides an electrode plate, which comprises the adhesive of the first aspect of the present application. It comprises the adhesive of the first aspect of the present application. The electrode plate can be manufactured by a method commonly used in the art.

[0118] It should be explained that the electrode plate of the present application may be a positive electrode plate or a negative electrode plate.

[0119] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the adhesive of the first aspect of the present application.

[0120] For example, a positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and a positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0121] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] In some embodiments, the positive electrode active material may be a positive electrode active material for batteries known in the art. For example, the positive electrode active material may include at least one of lithium-containing phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium transition metal oxide include lithium cobalt oxide (e.g., LiCoO2), lithium nickel oxide (e.g., LiNiO2), lithium manganese oxide (e.g., LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (e.g., LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2(NCM 333 (may be abbreviated as LiNi 0.5 Co 0.3 Mn 0.2 O2(NCM 523 (may be abbreviated as LiNi 0.5 Co 0.25 Mn 0.25 O2(NCM 211 (may be abbreviated as LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM 622 (may be abbreviated as LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM 811 Lithium nickel cobalt aluminum oxide (e.g., LiNi 0.85 Co 0.15 Al 0.05 Examples of the lithium-containing phosphate having an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0123] In some embodiments, the positive electrode plate can be manufactured in the following manner: The components for manufacturing the positive electrode plate, such as the positive electrode active material, the conductive agent, the adhesive described in the first embodiment of the present application, and any other components are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, which is then coated on a positive electrode current collector, and the positive electrode plate is obtained after processes such as drying and cold pressing.

[0124] In some embodiments, the loading of the adhesive according to the first aspect of the present application in the positive plate is 1-3%, calculated based on the total weight of the positive membrane layer.

[0125] Similarly, the electrode plate of the present application may be a negative electrode plate, which includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including the adhesive according to the first aspect of the present application.

[0126] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0127] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0128] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based material, tin-based material, and lithium titanate. The silicone-based material may be selected from at least one of silicone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0129] In some embodiments, the negative electrode film layer further optionally comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0130] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0131] In some embodiments, the negative electrode plate can be manufactured in the following manner: The components for manufacturing the negative electrode plate, such as the negative electrode active material, the conductive agent, the adhesive described in the first aspect of the present application, and any other components are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0132] In some embodiments, optionally, the amount of the adhesive according to the first aspect of the present application in the negative plate is 1-3%, calculated based on the total weight of the negative membrane layer.

[0133] According to a fourth aspect, an embodiment of the present application provides an electrode assembly, which comprises at least one of the adhesive of the embodiment of the first aspect of the present application, the separator of the embodiment of the second aspect, and the electrode plate of the embodiment of the third aspect. The electrode assembly proposed in the present application has all the beneficial effects of the adhesive and will not be further described here.

[0134] According to a fifth aspect, an embodiment of the present application provides a battery cell, the battery cell including an electrode assembly according to an embodiment of the fourth aspect of the present application.

[0135] Generally, a battery cell includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions shuttle between the positive electrode plate and the negative electrode plate to store and release ions. The electrolyte functions to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and mainly functions to prevent short circuit between the positive and negative electrodes and allows ions to pass through.

[0136] The battery cell can be manufactured by a method commonly used in the art, for example, by manufacturing a positive electrode plate, a negative electrode plate and a separator into an electrode assembly by a winding process or a lamination process, and then injecting an electrolyte into the electrode assembly and sealing it to manufacture a battery cell.

[0137] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0138] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.

[0139] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0140] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0141] In some embodiments, the electrolyte solution may further include optional additives, for example, additives for forming a negative electrode film, additives for forming a positive electrode film, and additives for improving some performance of the battery, such as additives for improving the overcharge performance of the battery, additives for improving the high temperature or low temperature performance of the battery, etc.

[0142] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0143] In some embodiments, the battery cell may include an exterior body that may be used to package the electrode assembly and electrolyte.

[0144] In some embodiments, the battery cell housing may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The battery cell housing may be a pouch, such as a bag-like pouch. The pouch may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0145] The present application is not particularly limited to the shape of the battery cell, which may be cylindrical, rectangular, or any other shape. For example, FIG. 1 shows a battery cell 5 with a rectangular structure as an example.

[0146] In some embodiments, referring to FIG. 2, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the battery cell 5 may be one or more, and can be selected by those skilled in the art according to specific actual needs.

[0147] According to a sixth aspect, an embodiment of the present application provides a battery, the battery including a battery cell according to the embodiment of the fifth aspect of the present application, and the specific expression form of the battery may be a battery module and a battery pack, and the number of battery cells included in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0148] Fig. 3 shows an example of a battery module 4. Referring to Fig. 3, in the battery module 4, a plurality of battery cells 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, the battery cells 5 may be arranged in any other manner. Furthermore, the plurality of battery cells 5 may be fixed by fasteners.

[0149] In an optional embodiment, the battery module 4 may further include a housing having an accommodating space, and the plurality of battery cells 5 are accommodated in the accommodating space.

[0150] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number may be selected by one skilled in the art according to the application and capacity of the battery pack.

[0151] 4 and 5 show an example of a battery pack 1. Referring to FIG. 4 and FIG. 5, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0152] According to a seventh aspect, an embodiment of the present application provides a power consuming device, the power consuming device comprising a battery cell according to an embodiment of the fifth aspect of the present application or a battery according to an embodiment of the sixth aspect.

[0153] The battery cells and batteries may be used as a power source for the power consuming devices, or as an energy storage unit for the power consuming devices, which may include, but are not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0154] The power consumption device can be a secondary battery, a battery module, or a battery pack depending on its usage demand.

[0155] 6 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power output and high energy density of the secondary battery of the power consumption device.

[0156] Another example of the device may be a mobile phone, a tablet computer, a notebook computer, etc. These devices are generally required to be thin, and may employ a secondary battery as a power source.

[0157] The technical solution of the present invention will be described in more detail below with reference to specific examples and drawings. It should be understood that the following examples are only for interpreting the present invention, and are not intended to limit the present invention.

[0158] The relevant parameters of the adhesives of Examples 1 to 25 and Comparative Examples 1 to 4 are shown in Table 1 below, and the parameters of the silicon dioxide of Examples 21 to 25 are shown in Table 2.

[0159] [Table 1] JPEG2025511417000011.jpg204142JPEG2025511417000012.jpg203140JPEG2025511417000013.jpg205142JPEG2025511417000014.jpg83142

[0160] [Table 2]

[0161] Example 1 [Production of polymer component 1] According to the weight percentage, the required monomers were mixed uniformly by stirring in the ratio of 45%wt of 2-hydroxyethyl acrylate, 40%wt of n-butyl acrylate, 8%wt of methyl methacrylate, 2%wt of acrylic acid, and 5%wt of trimethylolpropane triacrylate. 1000g of mixed monomers, 30g of sodium dodecyl sulfate emulsifier, 10g of ammonium persulfate initiator, and 1200g of deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ under nitrogen gas protection and reacting for 4h, the pH was adjusted to 6-8, and the temperature was lowered to below 40℃ to discharge the material. Polymer 1 was obtained.

[0162] [Manufacture of separator adhesive 1] 1 kg of polymer 1 was taken, 450 g of silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then ground to obtain separator adhesive 1.

[0163] [Manufacture of separator 1] The separator adhesive 1 is dispersed in water according to the ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0164] Example 2 [Production of polymer component 2] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of butyl methacrylate 65%wt, trimethylolpropane triacrylate 5%wt, acrylonitrile 15%wt, acrylic acid 2%wt, 2-hydroxyethyl acrylate 3%wt, and acrylamide 10%wt. 1000g of mixed monomers, 30g of sodium dodecyl sulfate emulsifier, 10g of ammonium persulfate initiator, and 1200g of deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ under nitrogen gas protection and reacting for 4h, the pH was adjusted to 6-8, and the temperature was lowered to below 40℃ to discharge the material. Polymer 2 was obtained.

[0165] [Manufacture of separator adhesive 2] 1 kg of polymer 2 was taken, 193 g of aluminum oxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 2.

[0166] [Manufacture of separator 2] The separator adhesive 2 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0167] Example 3 [Production of polymer component 3] According to the weight percentage, the required monomers were mixed uniformly by stirring in the ratio of 55%wt lauryl methacrylate, 2%wt acrylic acid, 3%wt 2-hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, 20%wt acrylonitrile, and 15%wt acrylamide. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After 4h reaction at 75℃ under the protection of nitrogen gas, the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 3 was obtained.

[0168] [Manufacture of separator adhesive 3] 1 kg of the polymer 3 material prepared in Example 3 was taken, 112 g of aluminum oxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 3.

[0169] [Manufacture of separator 3] The separator adhesive 3 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0170] Example 4 [Production of polymer component 4] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of 40%wt methyl methacrylate, 40%wt lauryl methacrylate, 3%wt acrylic acid, 2%wt 2-hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, and 10%wt acrylonitrile. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ under nitrogen gas protection and reacting for 4h, the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 4 was obtained.

[0171] [Manufacture of separator adhesive 4] Taking 1 kg of polymer 4, adding 24 g of nano silicon dioxide and 1 kg of deionized water, stirring for 1 hour, spray drying to produce adhesive powder, which is then polished and pulverized to obtain separator adhesive 4.

[0172] [Manufacture of separator 4] The separator adhesive 4 is dispersed in water according to the ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0173] Example 5 [Production of polymer component 5] According to the weight percentage, the required monomers were mixed uniformly by stirring in the ratio of 40%wt methyl methacrylate, 40%wt lauryl methacrylate, 3%wt acrylic acid, 2%wt 2-hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, and 10%wt acrylonitrile. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ and reacting for 4h under nitrogen gas protection, the pH was adjusted to 6-8, and the temperature was lowered to below 40℃ to discharge the material. Polymer 5 was obtained.

[0174] [Manufacture of separator adhesive 5] 1 kg of polymer 5 was taken, 50 g of sodium sulfate and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 5.

[0175] [Manufacture of separator 5] The separator adhesive 5 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0176] Example 6 [Production of polymer component 6] According to the weight percentage, the required monomers were mixed uniformly by stirring in the ratio of 25%wt lauryl methacrylate, 35%wt lauryl acrylate, 2%wt acrylic acid, 3%wt 2-hydroxypropyl acrylate, 5%wt trimethylolpropane triacrylate, and 30%wt acrylonitrile. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After 4h reaction at 75℃ under the protection of nitrogen gas, the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 6 was obtained.

[0177] [Manufacture of separator adhesive 6] 1 kg of polymer 6 was taken, 50 g of nano-silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then ground to obtain separator adhesive 6.

[0178] [Manufacture of separator 6] The separator adhesive 6 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0179] Example 7 [Production of polymer component 7] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of 10%wt n-butyl acrylate, 55%wt lauryl acrylate, 10%wt methyl methacrylate, 2%wt acrylic acid, 3%wt 2-hydroxypropyl acrylate, 5%wt trimethylolpropane triacrylate, 5%wt acrylonitrile, and 5%wt acrylamide. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. Under the protection of nitrogen gas, the temperature was raised to 75℃ and reacted for 4h, then the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 7 was obtained.

[0180] [Manufacture of separator adhesive 7] 1 kg of polymer 7 was taken, 50 g of nano-silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then ground to obtain separator adhesive 7.

[0181] [Manufacture of separator 7] The separator adhesive 7 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0182] Example 8 [Production of polymer component 8] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of 10%wt n-butyl acrylate, 55%wt lauryl acrylate, 10%wt methyl methacrylate, 2%wt acrylic acid, 3%wt 2-hydroxypropyl acrylate, 5%wt trimethylolpropane triacrylate, 5%wt acrylonitrile, and 5%wt acrylamide. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. Under the protection of nitrogen gas, the temperature was raised to 75℃ and reacted for 4h, then the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 8 was obtained.

[0183] [Manufacture of separator adhesive 8] 1 kg of polymer 8 was taken, 4.5 g of nano silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 8.

[0184] [Manufacture of separator 8] The separator adhesive 8 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0185] Example 9 [Production of polymer component 9] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of 65%wt lauryl acrylate, 10%wt methyl methacrylate, 2%wt acrylic acid, 3%wt 2-hydroxypropyl acrylate, 5%wt trimethylolpropane triacrylate, 10%wt acrylonitrile, and 5%wt acrylamide. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After 4h reaction at 75℃ under the protection of nitrogen gas, the pH was adjusted to 6-8, the temperature was lowered to below 40℃, and the material was discharged. Polymer 9 was obtained.

[0186] [Manufacture of separator adhesive 9] 1 kg of polymer 9 was taken, 50 g of aluminum oxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 9.

[0187] [Manufacture of separator 9] The separator adhesive 9 is dispersed in water according to the compounding ingredients to obtain a slurry, and the slurry is applied onto a separator material, and then the water is removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0188] Example 10 [Production of polymer component 10] According to the weight percentage, the required monomers were mixed uniformly by stirring in the ratio of 30%wt lauryl acrylate, 20%wt butyl acrylate, 2%wt acrylic acid, 3%wt 2-hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, and 40%wt acrylamide. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ and reacting for 4h under nitrogen gas protection, the pH was adjusted to 6-8, and the temperature was lowered to below 40℃ to discharge the material. Polymer 10 was obtained.

[0189] [Manufacture of separator adhesive 10] 1 kg of polymer 10 was taken, 0.45 g of sodium benzoate and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 10.

[0190] [Manufacture of separator 10] The separator adhesive 10 can be dispersed in water according to the ingredients to obtain a slurry, and then the slurry can be applied onto a separator material, and then the water can be removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0191] Example 11 [Production of polymer component 11] According to the weight percentage, the required monomers were mixed uniformly by stirring in the proportions of 20%wt methyl methacrylate, 50%wt n-butyl acrylate, 2%wt acrylic acid, 3%wt hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, 5%wt acrylonitrile, and 15%wt styrene. 1000g mixed monomers, 30g sodium dodecyl sulfate emulsifier, 10g ammonium persulfate initiator, and 1200g deionized water were added to a 5000mL four-neck flask equipped with a stirrer, thermometer, and condenser, and emulsified for 30min by stirring at high speed. After heating to 75℃ and reacting for 4h under nitrogen gas protection, the pH was adjusted to 6-8, and the temperature was lowered to below 40℃ to discharge the material. Polymer 11 was obtained.

[0192] [Manufacture of separator adhesive 11] 1 kg of polymer 11 was taken, 24 g of silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce adhesive powder, which was then polished and pulverized to obtain separator adhesive 11.

[0193] [Manufacture of separator 11] The separator adhesive 11 can be dispersed in water according to the ingredients to obtain a slurry, and then the slurry can be applied onto a separator material, and then the water can be removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0194] Example 12 [Production of polymer component 12] 10g sodium dodecyl sulfate, 1200g deionized water, 10g cumene hydroperoxide, 15g Rongalite, 0.05g ferrous sulfate, 2g EDTA disodium salt, and further mixed monomers of 20%wt methyl methacrylate, 40%wt n-butyl acrylate, 2%wt acrylic acid, 3%wt hydroxyethyl acrylate, 5%wt trimethylolpropane triacrylate, 10%wt acrylonitrile, and 10%wt styrene according to weight percentage were added, and then put into a high-pressure reactor, replaced with nitrogen gas three times, and then added 10%wt butadiene, emulsified at 25℃ with high speed stirring for 30min, heated to 65℃, reacted at 0.2Mpa for 6h, adjusted to Ph=6-8, cooled to below 40℃, and discharged the material. Polymer 12 was obtained.

[0195] [Manufacture of separator adhesive 12] 1 kg of polymer 12 was taken, 24 g of silicon dioxide and 1 kg of deionized water were added, and the mixture was stirred for 1 hour. After that, the mixture was spray-dried to produce an adhesive powder, which was then polished and pulverized to obtain separator adhesive 12.

[0196] [Manufacture of separator 12] The separator adhesive 12 can be dispersed in water according to the ingredients to obtain a slurry, and then the slurry can be applied onto a separator material, and then the water can be removed through drying and weighing, that is, the separator described in the present application can be obtained.

[0197] The preparation of the polymer, adhesive and separator of Examples 13 to 25 is the same as that of Example 3, the difference being that they follow the parameters of Table 1.

[0198] The preparation of the polymer, adhesive and separator of Comparative Examples 1 to 4 is the same as that of Example 1, the difference being that they follow the parameters of Table 1.

[0199] The separators of Examples 1 to 25 and Comparative Examples 1 to 4 are subjected to the following tests.

[0200] 1. The adhesive obtained in Example 1 was subjected to a scanning electron microscope treatment, and Figs. 7 and 8 were obtained. Referring to Fig. 7, it can be seen that the obtained adhesive as a whole is spherical. As can be seen from the enlarged view (Fig. 8), the adhesive has an organic polymer skeleton, the surface is uneven, and small sesame-like particles are attached to the surface, that is, it is inorganic.

[0201] 2. Ionic conductivity test: The separator is cut into 40 mm × 20 mm test pieces, and the cut separator is stacked to make a set of 4 layers. The separator is completely wetted with commercial electrolyte, and the test symmetric battery is assembled in a glove box. The separator resistance is tested using an electrochemical workstation, the measurement range is between 1 Hz and 100,000 Hz, and the applied AC signal polarization is 5 mV. The ionic conductivity can be calculated according to the AC resistance test result, and the formula is as follows: δ=1000L / RA where δ is the ionic conductivity in mS / cm and A is the area of ​​the test separator in cm 2 where L represents the thickness of the test separator and R represents the resistance of the test separator, and the results are shown in Table 1.

[0202] 3, Particle size test: Refer to the standard GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method. Use a laser granulometer (Malvern 3000, MasterSizer 3000) to test, and use a helium-neon red light source as the main light source. Take one clean small beaker, add 1g of the sample to be tested, add one drop of surfactant, add 20ml of deionized water (ensure the sample concentration is 8-12% light blocking), and sonicate at 53KHz / 120W for 5min to ensure the sample is completely dispersed. Turn on the laser granulometer and automatically test the background after cleaning the light path system. Stir the already sonicated solution to be tested, disperse it evenly, and put it into the sample pool as required, and start to measure the particle size. The measurement result can be read from the instrument.

[0203] The particle size distribution was calculated based on the particle size and the results are shown in Table 1.

[0204] 4. Vitrification temperature test (DSC method) Reference standard: GB / T 19466.2 Differential Scanning Calorimetry (DSC) - Determination of glass transition temperature.

[0205] Test conditions: (1) Sample preparation: 6±0.05 mg of sample was weighed into an Al crucible, shaken flat, covered, and placed in a measuring instrument. (2) Parameter settings: nitrogen gas atmosphere, purification gas rate is 50 mL / min, protective gas rate is 100 mL / min; (3) Temperature rise conditions: the temperature rise rate is 10°C / min, and the temperature range is -40 to 200°C.

[0206] 5. The negative electrode plate, the positive electrode plate, the electrolyte and the separator are assembled into a button battery, and the cycle capacity retention rate is measured. The measurement method is as follows:

[0207] Take the lithium ion battery in the examples and comparative examples, and ensure that each example has at least two parallel samples. First, place the battery in a constant temperature environment of 25 ° C and leave it for 1 hour. Then, perform constant current charging on the battery at a charge rate of 2C, charge to 3.65V, and then switch to constant voltage charging. When the charging current is lower than 0.05C, stop charging and leave it for 5 minutes. Then, discharge the battery at a constant current of 1C to 2.5V and leave it for 5 minutes. The above flow is a certain number of cycles (here 1000 cycles), and the capacity retention rate is calculated as the capacity retention rate at the nth cycle = the discharge capacity at the nth cycle / the discharge capacity at the 2nd cycle * 100%.

[0208] The test results are shown in Table 3.

[0209] [Table 3] JPEG2025511417000017.jpg81113

[0210] As can be seen from Table 3, by comparing the comparative examples with the examples, and as can be seen from Examples 1 to 25, the adhesive includes a first glass transition temperature and a second glass transition temperature within the range of -10 to 95°C, and the first glass transition temperature is higher than the second glass transition temperature. Due to the cooperation of the organic polymer and the inorganic material, the obtained adhesive has good adhesive performance and an appropriate glass transition temperature, which is suitable for fully exerting its adhesive performance under battery operating conditions, further contributing to improving the dynamic performance and safety performance of the battery, and further improving the battery cycle capacity retention rate.

[0211] When the glass transition temperatures of Comparative Examples 1 to 4 are not within the range between the first and second glass transition temperatures, the cycle performance of the battery is significantly reduced, which shows that the simultaneous use of organic and inorganic materials and the first and second glass transition temperatures play an important role.

[0212] In summary, the adhesive proposed in this application is a combination of an organic polymer and an inorganic material, and the resulting adhesive has good adhesive performance and an appropriate glass transition temperature, which makes it suitable for fully exerting its adhesive performance under battery operating conditions, and further contributes to improving the dynamic performance and safety performance of the battery.

[0213] The above is only a preferred embodiment of the present invention, and is not intended to limit the scope of the present invention, and those skilled in the art can make various modifications and variations to the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included in the patent protection scope of the present invention. [Explanation of symbols]

[0214] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 battery cell, 51 case, 52 electrode assembly, 53 cover plate.

Claims

1. 1. An adhesive comprising an organic polymer and an inorganic material, the adhesive having a first vitrification transition temperature and a second vitrification transition temperature within a range of −10 to 95° C., the first vitrification transition temperature being greater than the second vitrification transition temperature.

2. The adhesive has a first glass transition temperature of 30 to 75° C.; and / or The adhesive has a second glass transition temperature of −10 to 25° C.; and / or 2. The adhesive according to claim 1, wherein the inorganic substance is attached to a surface of the organic polymer and / or dispersed within the organic polymer.

3. The polymerized monomers of the organic polymer include a first monomer, and the structural formula of the first monomer is as follows: Here, R 1 contains a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R 2 comprises a substituted or unsubstituted alkyl group having 1 to 15 carbon atoms, a cycloalkyl group having 3 to 6 carbon atoms, or an isobornyl group, and in the case of substitution, the substituent comprises a hydroxyl group or an alkyl group having 1 to 6 carbon atoms.

4. 4. The adhesive of claim 3, wherein the first monomer comprises at least one of methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, trifluoroethyl methacrylate, glycidyl methacrylate, and trimethylolpropane triacrylate.

5. 5. The adhesive of claim 3 or 4, wherein the first monomer comprises at least one of methyl methacrylate, lauryl acrylate, lauryl methacrylate, and trimethylolpropane triacrylate.

6. The polymerized monomers of the organic polymer further comprise a second monomer, the second monomer comprising an organic material containing an unsaturated nitrile group; and / or The polymerized monomers of the organic polymer further include a third monomer, the third monomer including an organic material containing an unsaturated amide group; and / or 6. The adhesive of claim 3, wherein the polymerized monomers of the organic polymer further comprise a fourth monomer, the fourth monomer comprising an organic material containing an unsaturated alkenyl group.

7. The polymerized monomers of the organic polymer further include a second monomer, and the structural formula of the second monomer is as follows: Here, R 3 contains a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, and / or The polymerized monomers of the organic polymer further include a third monomer, and the structural formula of the third monomer is as follows: Here, R 4 contains a hydrogen atom or an alkyl group of 1 to 6 carbon atoms, R 5 contains a hydrogen atom, an alkyl group of 1 to 6 carbon atoms substituted with a hydroxyl group, or an alkoxy group of 1 to 6 carbon atoms, and / or The polymerized monomers of the organic polymer further include a fourth monomer, and the structural formula of the fourth monomer is as follows: Here, R 6 , R 7 , R 8 , R 9 The adhesive according to any one of claims 3 to 6, characterized in that each independently contains a hydrogen atom, a substituted or unsubstituted phenyl group, a substituted or unsubstituted cycloalkyl group, or a linear or branched alkyl group.

8. The polymerized monomers of the organic polymer further comprise a second monomer, the second monomer comprising at least one of acrylonitrile, methacrylonitrile, ethacrylonitrile, and / or The polymerized monomers of the organic polymer further include a third monomer, the third monomer including at least one of acrylamide, N-methylolacrylamide, and N-butoxymethacrylamide; and / or 7. The adhesive of claim 3, wherein the polymerized monomers of the organic polymer further comprise a fourth monomer, the fourth monomer comprising at least one of ethylene, styrene, butadiene, and isoprene.

9. The polymerized monomers of the organic polymer further comprise a second monomer, the second monomer comprising at least one of acrylonitrile and methacrylonitrile; and / or 7. The adhesive of claim 3, wherein the polymerized monomers of the organic polymer further comprise a third monomer, the third monomer comprising at least one of acrylamide and N-methylol acrylamide.

10. 7. The adhesive according to claim 3, wherein the polymerized monomers of the organic polymer further comprise a second monomer and a third monomer, the second monomer comprises an organic material containing an unsaturated nitrile group, and the third monomer comprises an organic material containing an unsaturated amide group, and a weight ratio of the first monomer, the second monomer, and the third monomer is 1:0-0.8:0-0.

15.

11. 11. The adhesive according to claim 10, wherein a weight ratio of the first monomer, the second monomer, and the third monomer is 1:0.05-0.2:0.05-0.

1.

12. 7. The adhesive according to claim 3, wherein the polymerized monomers of the organic polymer further include a second monomer, a third monomer, and a fourth monomer, the second monomer includes an organic material containing an unsaturated nitrile group, the third monomer includes an organic material containing an unsaturated amide group, and the fourth monomer includes an organic material containing an unsaturated alkenyl group, and a weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0-0.8:0-0.7:0-0.

5.

13. 13. The adhesive of claim 12, wherein a weight ratio of the first monomer, the second monomer, the third monomer, and the fourth monomer is 1:0.05-0.6:0.05-0.3:0-0.

2.

14. The particle size of the adhesive satisfies 3 μm≦D50≦10 μm, and / or the particle size distribution of the adhesive=(D90-D10) / D50, the particle size distribution being less than or equal to 2.5; and / or 3. The adhesive according to claim 1, wherein the particle size of the inorganic substance is 0.0001 μm to 2 μm.

15. the particle size distribution of the adhesive=(D90-D10) / D50, the particle size distribution being smaller than 2; and / or The particle size of the inorganic material is 0.01 μm to 0.5 μm, and / or 3. The adhesive of claim 1 or 2, wherein the inorganic material comprises at least one of oxides of silicon, oxides of aluminum, oxides of calcium, oxides of zinc, oxides of magnesium, sodium sulfate, sodium benzoate, calcium carbonate, and modifiers thereof.

16. the particle size distribution of the adhesive=(D90-D10) / D50, the particle size distribution being smaller than 1.8; and / or The particle size of the inorganic material is 0.01 μm to 0.2 μm, and / or The mass percentage of the organic polymer is 50% to 99.9% based on the mass of the adhesive; and / or 3. The adhesive according to claim 1, wherein the inorganic material includes at least one of silicon dioxide, aluminum oxide, zinc oxide, magnesium oxide, and sodium benzoate.

17. Based on the mass of the adhesive, the mass proportion of the organic polymer is 60% to 99%; and / or 3. The adhesive according to claim 1, wherein the inorganic substance includes at least one of fumed silicon dioxide, silicon fine powder, aluminum oxide, and sodium benzoate.

18. and / or the mass percentage of the organic polymer is 70% to 99% based on the mass of the adhesive; 3. The adhesive according to claim 1, wherein the inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is from 2 nm to 1 μm.

19. the outer surface of the adhesive is roughened; and / or 3. The adhesive according to claim 1, wherein the inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 100 nm.

20. The ionic conductivity of the adhesive is 0.3 to 0.6 mS cm -1 and / or 3. The adhesive according to claim 1, wherein the inorganic material contains silicon dioxide, and the particle size of the silicon dioxide is 5 nm to 20 nm.

21. A separator comprising the adhesive of any one of claims 1 to 20.

22. 21. A plate comprising an adhesive according to any one of claims 1 to 20.

23. 23. An electrode assembly, comprising at least one of the adhesive according to any one of claims 1 to 20, the separator according to claim 21 and the electrode plate according to claim 22.

24. A battery cell comprising the electrode assembly of claim 23.

25. A battery comprising the battery cell of claim 24.

26. 26. A power consuming device comprising a battery cell according to claim 24 or a battery according to claim 25.

Citation Information

Patent Citations

  • Water-based paint for lithium ion battery composite diaphragm, lithium ion battery composite diaphragm and lithium ion battery

    CN112940650A

  • Battery diaphragm and preparation method thereof, battery and preparation method of core-shell type sphere

    CN113410576A

  • Adhesive agent for lithium ion secondary batteries, lithium ion secondary battery separator, and lithium ion secondary battery

    JP2015028842A

  • Method of manufacturing separator for power storage device

    JP2016072155A

  • Aqueous Binder for Lithium-Ion Batteries, Preparation Method and Use Thereof

    JP2018527710A